Placental Histopathology and Clinical Presentation of Severe Congenital Zika Syndrome in a Human Immunodeficiency Virus-Exposed Uninfected Infant - Rabelo, Kíssila; de Souza Campos Fernandes, Regina Célia; Souza, Luiz José de; Louvain de Souza, Thais; Santos, Flávia Barreto dos; Guerra Nunes, Priscila Conrado; Azeredo, Elzinandes Leal de; Salomão, Natália Gedeão; Trindade, Gisela Freitas; Basílio-de-Oliveira, Carlos A.; Carvalho, Jorge José de; Medina-Acosta, Enrique; et al. (Frontiers in Immunology, 2017)
In the large Zika virus (ZIKV) epidemic that occurred in Brazil in 2015, intrauterine fetal exposure to ZIKV was associated with a significant risk of developing microcephaly and neurological disorders in the infected infants. ZIKV-associated disease has since been reported in 24 countries in the Americas. At present, definitive evidence is lacking regarding intrauterine co-exposure to ZIKV and other viral infections and whether such co-infection impacts the risk of acquiring either infection or disease severity. Here, we provide evidence of intrauterine exposure to both ZIKV and HIV infection, causing congenital Zika syndrome in an HIV-exposed uninfected infant. Clinical, imaging and laboratory examinations of the pregnant woman and the newborn were performed. Histopathology, ZIKV/HIV-specific immunoassays, and ultrastructural evaluation of the placenta were performed. The Zika-asymptomatic, HIV-positive pregnant woman underwent ultrasounds revealing fetal cerebral ventriculomegaly, microcephaly, and brain atrophy. Her baby girl was born small for gestational age and with the neurological sequelae of congenital Zika syndrome. The evaluation of the abnormally large term placenta revealed severe damage to the maternal decidua and chorionic villi, cells positive for ZIKV-specific antigens but not HIV antigens, and intracellular membranous clusters of virus-like particles approximately 25 nm in diameter. The rapid progression and severity of the congenital Zika syndrome may be related to the uncontrolled HIV disease in the mother. The poor inflammatory response observed in the placenta may have reduced the inherent risk of mother-to-child transmission of HIV.